Statistical damage constitutive model of cemented sand and gravelbased on a modified spatially mobilized plane yield criterion - Jiangui Yang; Honglei Ren; Qiang Li; Shuling Cai (Case Studies in Construction Materials)
Cemented sand and gravel (CSG) holds significant potential for application in dam construction; however, research into its mechanical properties remains insufficient. Moreover, there is a scarcity of constitutive models that accurately reflect these properties. In this study, a comprehensive series of triaxial shear tests on CSG were conducted, leading to the development of a constitutive model specifically tailored for this material. The results indicate that CSG exhibit pronounced strain-softening and dilatancy characteristics, both of which are intensified with increasing gel content. The Spatially Mobilized Plane (SMP) yield criterion is modified by analyzing the variation laws of cohesive c and friction angle φ of CSG with respect to varying gel content. This modified criterion is then used to describe the failure criterion of micro-element strength. Based on the discrete and stochastic distribution of microdefects in CSG, it is assumed that the strength of the Microscopic elements follows a WeibullWeibull distribution. A constitutive model reflecting the entire damage process of CSG is established based on statistical and continuous damage mechanics theories.The model parameters were determined using conventional triaxial test data. The physical significance of the WeibullWeibull distribution parameters m and F0 was examined, and the variation of these parameters with respect to gel content and confining pressure was analyzed and modified. Finally, the predicted results of the proposed model were compared with experimental values and those from other constitutive models. The findings indicate that the proposed model accurately simulates both the stress-strain curve and the volumetric strain curve of CSG. Specifically, in modeling the strain softening and dilatancy behavior of CSG, the proposed model demonstrates a clear advantage over other existing models.